Building The Entepreneural Spirit of Local Community to Manage Lake Limboto as Sustainable Public Asset - Lamangida, Trisusanti; Tilome, Apris Ara; Machmud, Joice (Asosiasi Fakultas Ekonomi dan Bisnis Perguruan Tinggi Muhammadiyah, 2019)
Lake Limboto is a vital public asset that concerns the lives of many people hence it is important for the government to pay serious attention and proper management on it. Furthermore, three parties are closely linked to the sustainability of this public asset. Building the entrepreneurial spirit of the local community to manage Lake Limboto should be addressed to be the inspiration and new spirit of the entrepreneurial community as a sustainable investment. This study aims to analyzeand explain the importance of building the community entrepreneurial spirit on the management of Lake Limboto as a sustainable investment, particularly in the economic empowerment of local community. Data were collected using FGD technique, literature studies, and field observation. The analysis was conducted using qualitative descriptive approach. This study revealed the development of community business groups or creative-innovative behavior of consumers in managing Lake Limboto. In the implementation, innovation becomes more valuable in building creativity and innovation, particularly in building the entrepreneurial spirit in managing Lake Limboto as a public and regional asset in the present and the future. The theoretical implication is to reaffirm Schumpeter’s theory of innovation. In association with the economic empowerment and development of community, entrepreneurship is aspired to realize human resources who arereliable, professional, highly motivated with the need of achievement, risk takers, innovative and independence. It entails the abilities to create new products and services in the market, new place of business transaction, new buyers, new market leader, and to support economic development.